A numerical analysis of Ephedra L. based on reproductive features - Yang, Yong (Bangladesh Journal of Plant Taxonomy, 2013)
A numerical analysis of Ephedra L. was conducted based on 29 characters of reproductive organs. The results indicate that species are not grouped according to their geographic ranges, sect. Alatae is in one group, sect. Asarca excluding E. cutleri and E. viridis consists of a Eu-asarca group while sect. Ephedra plus E. cutleri and E. viridis of the traditional sect. Asarca make up a third expanded Ephedra group. The Old World sect. Monospermae including E. rhytidosperma, E. equisetina, E. nebrodensis, E. monosperma and E. procera was rediscovered in this study while those Himalayan endemic species (e.g. E. minuta, E. likiangensis, E. saxatilis, E. dawuensis and E. gerardiana) used to be grouped in the Old World sect. Monospermae are clustered together with sect. Scandentes including E. foeminea, E. ciliata, E. altissima and E. fragilis. This study further confirms that the adaptive seed dispersal syndromes of sect. Asarca have originated for not only once. Some new features are introduced as related to dispersal, e.g. weight and size of seeds, and nature and thickness of the outer envelope. DOI: http://dx.doi.org/10.3329/bjpt.v20i1.15464 Bangladesh J. Plant Taxon. 20(1): 51-60, 2013 (June)